Sex-bias in COVID-19-associated illness severity and mortality in cancer patients: A systematic review and meta-analysis. (September 2020) - Park, Robin; Chidharla, Anusha; Mehta, Kathan; Sun, Weijing; Wulff-Burchfield, Elizabeth; Kasi, Anup
Abstract: Background: Whether there is sex-bias within the adverse outcomes associated with COVID-19 in the cancer population is unknown. In this regard, several published studies have examined this question, but the results are inconclusive and inconsistent. To evaluate the sex-difference in the risk of adverse outcomes associated with COVID-19 in the cancer population, we have conducted a systematic review and meta-analysis. Methods: Published articles evaluating adverse outcomes associated with COVID-19 in the cancer population from inception to June 2020 were identified by searching PubMed and EMBASE, ASCO 2020 Virtual Annual Conference, AACR 2020 COVID-19 and Cancer, ESMO conferences held from January to June 2020, and medRxiv and bioRxiv. Prospective or retrospective analyses in English, providing outcomes data with sex differences in the cancer population were included. The primary outcomes of interest were pooled ORs of severe illness, all-cause death, and the composite of severe illness and death attributable to COVID-19 in males versus females in cancer patients. Findings: Overall, 3968 patients (17 studies) were analyzed in retrospective study settings. Overall, pooled ORs of the composite of severe illness and all-cause death in the setting of COVID-19 in males versus females was 1.60 (95% CI, 1.38–1.85). The risk of severe illness or death were both independently increased in males versus females. Interpretation: Male sex was associated with a higher risk of severe illness and death attributable to COVID-19. This finding has implications in informing the clinical prognosis and decision making in the care of cancer patients. Funding: This study received no funding.